THE STUDENT'S APPEARANCE STRATEGIES IN ONLINE ENGLISH AS A FOREIGN LANGUAGE CLASSROOM - Rusdiah (IAI DDI POLEWALI MANDAR, 2023)
Non-verbal communication, in particular appearance, is a strategy in online English as a Foreign Language classroom, shown to reflect social status, dignity, hierarchy, gender, and religion, all of which carry symbolic meaning for people. Unfortunately, this non-verbal communication to performance and pedagogy is lost in online classrooms. This study aimed to identify students’ appearance strategies in online English as a foreign language classroom with a mixed-method design. The instrument of this research involved interviews, passive participants, observation, and documentation. The subject of this research is undergraduate students of English education. To conduct a pilot study in an online EFL classroom using Zoom software, the researcher instantiated one such example of the entire system. There were 3 appearance strategies in online EFL classrooms, namely: work attire, casual attire, and evening attire. The presence of technology allows individuals to interact with each other indirectly, or what is known as interaction in virtual space. However, students must be mastered in online EFL classrooms. It includes the appearance strategies that should be applied as long as the platform is supported